4 Laws of New Hampshire, Revolutionary Period 39-42 (Henry Harrison Metcalf ed., 1916) - (:unkn) unknown (My University, 1776)
An Act for forming and regulating the Militia within the State of New Hampshire in New England, and for repealing all the Laws heretofore made for that purpose: Retained the recently established age limits of 16 to 50. Any "good Fire Arm" was acceptable. Also mandatory was a "good Ramrod." The latter was used to ram the bullet down the muzzle, into the firing chamber. It was essential to the use of a muzzle-loading gun. While some militia statutes specified a ramrod, many left it to implication. By requiring that a gun be "well fixed" or "good," the less specific statutes implicitly required all appropriate accoutrements, including the ramrod. For gun cleaning, the worm and priming wire had long been mandated. The new laws had an additional item: a brush. Two types of edged weapons were needed. First, "a Bayonet fitted to his Gun." In close quarters fighting, an infantryman would attach the bayonet to the front of his gun. Then the gun would be used as a spear. Since there was a bayonet, there had to be "a Scabbard and Belt therefor." Besides the bayonet, one additional edged weapon was mandatory: "a Cutting Sword, or a Tomahawk or Hatchet." The ammunition items were: "Pouch containing a Cartridge Box, that will hold fifteen Rounds of Cartridges at least, a Hundred Buck Shot, a Jack Knife and Tow for Wadding, six Flints, one Pound of Powder, forty Leaden Balls fitted to his Gun." Finally, field supplies: "Knapsack and Blanket, a Canteen or Wooden Bottle sufficient to hold one Quart." Persons who were self-sufficient had to supply themselves with the required items. As for others, "all Parents, Masters, and Guardians, shall furnish and equip those of the Militia which are under their Care and Command
Keywords: MILITIAS; REQUIRED POSSESSION